Efecto del proceso de deshidratado del banano morado (red dacca) sobre las características nutricionales - Laz Vera, Daniela Anahi (2023)
The main objective of the research was to evaluate the effect of two methods of dehydration in purple bananas (Red Dacca) that were in two stages of maturation, on the nutritional characteristics, for which a completely randomized DCA design was applied with a bifactorial arrangement. AxB with 4 treatments and 4 repetitions, the measurements obtained were subjected to the Tukey test (P ≥ 0.05), the study factors were Factor A: stage of maturity and Factor B: pulp dehydration methods, phase The experimental study was developed in the bromatology laboratory of the Quevedo State Technical University. In the evaluation prior to banana processing (fresh) the results obtained in the bromatological analyzes in the dependent variables fat, energy and fiber, significant differences were observed in factor A, determining the incidence of the state of ripeness on these variables, therefore, The alternative hypothesis was accepted, while for the other variables there was no difference, regarding the processed (dehydrated) fruit, in the dependent variables ash, energy, fiber and polyphenols there was a significant difference in the independent factors and also in the variables. interactions, while in the other variables there were no differences, in this way it is concluded that the best treatment is the one that used green ripe bananas and dried in an oven. Keywords: bromatological, dehydrated, nutrition, healthy